Students’ Perception on Quizizz As Digital Game-Based Learning Tool For Formative Assessments - Tuti Purwati (JELLE : Journal Of English Literature, Linguistics, and Education, 2022)
This study is entitled “Students’ Perception on Quizizz as Digital Game-Based Learning Tool for Formative Assessments (A Study at the Tenth Grade of SMK Negeri 1 Wanareja in the Academic Year of 2021/2022)”. The study aimed at knowing how students’ perception on Quizizz as Digital Game-Based Learning tool and how Quizizz used for formative assessment. This research used a qualitative descriptive design. The subject of this research was the tenth-grade students of SMK Negeri 1 Wanareja in the academic year of 2021/2022. The population was 609 students divided into 17 classes consisted of 7 majors. The samples of this research were 150 students that were taken randomly from all classes. The data were collected using questionnaire, interview and document. Method triangulation was used as data validation technique. The result of this research showed that students gave positive responses on Quizizz as Digital Game-Based Learning tool dealing with students’ learning and engagement, rules and goals, clear outcomes and immediate feedback, and also students’ interaction. They also gave positive responses on Quizizz used for formative assessment in English class. Furthermore, the activities on Quizizz elicited evidence of learning, provided feedback as well as allowed students to own their learning.Keywords: students’ perception, Quizizz, Digital Game-Based Learning, formative assessment